2017
DOI: 10.1016/j.memsci.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid reactive distillation process with high selectivity pervaporation for butyl acetate production via transesterification

Abstract: A hybrid reactive distillation system with high selectivity pervaporation was examined to produce butyl acetate and methanol via transesterification of methyl acetate with butanol. High selectivity pervaporation was combined with reactive distillation to eliminate a hitherto required column for the separation of a methanol and methyl acetate azeotrope. The polyamide-6 membrane was used for this purpose because of its high selectivity for methanol while also allowing sufficient permeate flux. The high purity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 52 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The market demand for n-butyl acetate has grown in recent years, which has increased the price and profit margin. 12 Until today, the industrial production of n-butyl acetate mostly uses the traditional concentrated sulfuric acid-catalyzed esterification method. 13 Over the years, the potential of this method has been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The market demand for n-butyl acetate has grown in recent years, which has increased the price and profit margin. 12 Until today, the industrial production of n-butyl acetate mostly uses the traditional concentrated sulfuric acid-catalyzed esterification method. 13 Over the years, the potential of this method has been fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…As an important organic chemical, it is widely used as a food additive, an extractant, a coating agent, a pharmaceutical intermediate, and in other industries. The market demand for n -butyl acetate has grown in recent years, which has increased the price and profit margin …”
Section: Introductionmentioning
confidence: 99%
“…Sain et al used commercial a methanol‐selective cuprophane membrane to separate the methyl acetate–methanol mixture. Although a separation factor of up to 8.55 was obtained at 45°C, the flux was only 0.45 kg/(hr·m 2 ) at 5.9 wt.% methanol‐feed concentration, thus increasing the membrane cost and hindering its industrial application . Genduso et al reviewed eight methanol selective membranes that were previously reported in the classical literature.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the selectivity in the reactive distillation was 21% higher than that in the batch reactor. Moreover, the reactive distillation method could simultaneously achieve reaction and separation goals, which also reduced the investment and operating costs …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reactive distillation method could simultaneously achieve reaction and separation goals, which also reduced the investment and operating costs. [18][19][20][21][22][23][24][25] In the MPA reaction and separation system, there existed three kinds of binary azeotropes, namely MP-H 2 O, 26 MP-HAC 27 and MPA-H 2 O 4 mixtures, which increased the difficulties of the reactive distillation operation. Therefore a combination of extractive and reactive distillation was developed to separate the generated H 2 O from the system.…”
Section: Introductionmentioning
confidence: 99%